2021
DOI: 10.3390/ijerph18126188
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Parents towards Childhood Hearing Loss and Pediatric Hearing Services in Sharjah, United Arab Emirates

Abstract: The successful implementation of pediatric audiology services depends on parental engagement and support. It is essential to analyze the gaps in knowledge level and attitude of the parents in United Arab Emirates (UAE), towards pediatric hearing loss and pediatric audiology services. The present study aimed to assess the knowledge and attitude of parents in Sharjah, UAE.A cross-sectional survey was administered to 295 parents in a tertiary care hospital setting. The self-reported questionnaire consisted of 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
6
10
0
1
Order By: Relevance
“…These results were probably due to the high prevalence of otitis media with effusion in the developing countries, which lends ear discharge as a known cause of hearing loss (Olusanya et al, 2006 ). Similar to ear discharge, high fever was also highly recognized as a risk factor among mothers in the present study, which agreed with Wang et al, ( 2017 ) and Olusanya et al, ( 2006 ), but it was less frequently identified by mothers in other countries, such as the United Arab Emirates and Solomon Islands (Ayas & Yaseen, 2021 ; Swanepoel & Almec, 2008 ). Similar to the study by Wang et al, ( 2017 ), the reason for this high knowledge in the present study might be because of social knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results were probably due to the high prevalence of otitis media with effusion in the developing countries, which lends ear discharge as a known cause of hearing loss (Olusanya et al, 2006 ). Similar to ear discharge, high fever was also highly recognized as a risk factor among mothers in the present study, which agreed with Wang et al, ( 2017 ) and Olusanya et al, ( 2006 ), but it was less frequently identified by mothers in other countries, such as the United Arab Emirates and Solomon Islands (Ayas & Yaseen, 2021 ; Swanepoel & Almec, 2008 ). Similar to the study by Wang et al, ( 2017 ), the reason for this high knowledge in the present study might be because of social knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding ear discharge, our findings were consistent with Kaspar et al, ( 2017 ), Ayas & Yaseen ( 2021 ), Wang et al, ( 2017 ), Swanepoel & Almec ( 2008 ), Olusanya et al, ( 2006 ), and Alsudays et al, ( 2020 ), as a high percentage of mothers answered “yes” to the statement “Ear discharge can cause hearing loss”. These results were probably due to the high prevalence of otitis media with effusion in the developing countries, which lends ear discharge as a known cause of hearing loss (Olusanya et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations